Barriers to utilisation of antenatal care services in South Sudan: a qualitative study in Rumbek North County - Calistus Wilunda; Chiara Scanagatta; Giovanni Putoto; Francesca Montalbetti; Giulia Segafredo; Risa Takahashi; Serge André Mizerero; Ana Pilar Betrán (BMC, 2017)
Abstract Background Access to adequate antenatal care (ANC) is critical in ensuring a good maternal health and in preventing maternal and neonatal morbidity and mortality. South Sudan has one of the world's poorest health indicators due to a fragile health system and a combination of socio-cultural, economic, and political factors. This study was conducted to identify barriers to utilisation of ANC services in Rumbek North County. Methods Using a qualitative design, data were collected through 14 focus group discussions with 169 women and 45 men and 12 key informant interviews with community leaders, staff working in health facilities, and the staff of the County Health Department. Data were analysed using inductive content analysis. Results The perceived barriers to ANC utilisation were categorised as follows: 1) Issues related to access to health facilities and lack of resources. These included long distance to health facilities, lack of means of transportation to the health facilities, floods and poor roads, and demand for payment for health care at some health facilities; 2) The influence of the socio-cultural context and conflict including heavy burden of domestic chores, the negative influence of husbands who were reluctant to allow their wives to attend ANC, and insecurity; 3) Perceptions about pregnancy including misperceptions about the benefits of ANC and low perceived risk of pregnancy-related complications; and 4) Perceptions about the quality of care and the efficacy of medical treatment. Conclusions This study identified a myriad of factors deeply entrenched in the society, which prevent women from utilising ANC services. It also elicits broad aspects of interconnectedness among the barriers. To ensure effectiveness, strategies to improve utilisation of ANC in the study area and in similar contexts need to take into account the barriers identified by this study.